Pengaruh Perbandingan Tepung Tempe dan Tepung Tapioka Terhadap Karakteristik Bakso Vegetarian - Abdurrahman, Abdurrahman; Amelia, Lenny Amelia (Ma'soem University, 2025)
Vegetarian meatballs represent an innovative product aimed at utilizing tempeh as an alternative source of nutritional intake, particularly protein, in response to the widespread popularity of meatball-based products among the general public. This study aims to determine the effect of varying proportions of tempeh flour and tapioca flour on the characteristics of vegetarian meatballs and to identify the optimal formulation that yields the best overall quality. A randomized block design (RBD) was employed, consisting of five treatments with five replications each. Chemical analyses were conducted to measure moisture content, protein content, and dietary fiber content, while sensory evaluations were performed to assess the level of preference for aroma, taste, texture, and color. The results showed that the variation in tempeh and tapioca flour ratios significantly affected the characteristics of the tempeh meatballs. The best formulation, determined through a scoring test, was found in varying proportions oftempeh flour (45) and tapioca flour(55), which achieved a total score of 19.